DECREASE OF THE EXERGY DESTRUCTION IN AIR HEATERS IN BAGASSE BOILERS OF NATURAL DRAUGHT - Cruz Fonticiella, Oscar Miguel; González Petit Jean, Miguel Luis; Marín Hernández, Juan José; Gabriel García, Ulises (Centro Azúcar Journal, 2008)
Applying the second law of thermodynamics to the thermal systems, the exergy destruction is revealed. This paper presents a method that combines a simplified design of the air heaters with the exergoeconomics, showing a decrease of the exergy destruction in those equipments. It is applied in the bagasse boilers of natural draught, that present, in general, lack space, high electricity consumptions and a little financing for their remodeling.